THE RESULTS OF THE STUDY ROBUST DURABILITY THE CLOSED ACS THE DRYER FLUIDIZED BED - Fedotova, M.; Osadchy, S.; Skrynnik, I.; Berezyuk, I. (Енергетика і автоматика, 2016)
The article shows application of the method of the research robust stability of the closed-loop system of the example multidimensional object of management – the dryer fluidized bed, the design of which was developed in Kirovograd national technical University.